Selected immunological parameters in clinical evaluation of patients with atopic dermatitis - Rosińska-Więckowicz, Anna; Czarnecka-Operacz, Magdalena; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : It has been suggested that soluble immune receptors (SIRs) such as sCD25 and sCD30 may serve as potential biomarkers in evaluation of atopic dermatitis (AD). Previous studies clearly indicated that serum levels of interleukin (IL)-13 and total IgE (tIgE) might be potentially useful in the evaluation of patents with AD. Aim : To evaluate whether serum levels of sCD25 and sCD30 are suitable biomarkers of AD. Moreover, we have decided to estimate the usefulness of tIgE and IL-13 serum level determination in the evaluated population. Material and methods : A group of 102 AD patients was investigated. Serum concentrations of sCD30, sCD25, IL-13 and tIgE were measured. The clinical phenotype of AD was classified as extrinsic (ADe) or intrinsic (ADi) based on the presence of IgE. Statistical analysis was performed to estimate correlations between obtained results and clinical features of the population such as AD phenotype, age, disease extent and severity. Results : Extrinsic AD was diagnosed in 71% of patients, while ADi phenotype was observed in 29% of the investigated population. A negative correlation between serum levels of sCD25 and sCD30 and disease severity as well patients’ age was established. Serum levels of IL-13 did not reach the cut-off point set by the manufacturer. A positive correlation between serum levels of total IgE and disease severity and patients’ age was observed. Conclusions :This paper shows that serum levels of sCD25 and sCD30 as well as tIgE are age dependent. Determination of serum levels of sCD25, sCD30 and IL-13 is not useful in everyday practice.